IMMUNE RESPONSE AND TICK REJECTION PATTERN OF MIDGUT AND SALIVARY GLAND VACCINES AGAINST LOCALLY PREVALENT BOOPHILUS MICROPLUS TICKS - M. Asif; K. Saeed; K. Muhammad (Journal of Animal and Plant Sciences, 2011)
Midguts and salivary glands were isolated from partially engorged female ticks and processed for a vaccine candidate. The protein contents were measured and two different oil-based vaccines were prepared; midgut vaccine (MGV) and salivary gland vaccine (SGV). These vaccines were administered sub-cutaneously on days 0, 14 and 21. Their efficacy was monitored on the basis of antibody titers as determined by agar gel precipitation test. Ticks rejection on immunized hosts was evaluated in terms of attachment, mortality, oviposition, and hatchability of eggs. MGV offered significantly better control of B. microplus as compared to SGV. The highest antibody titers were observed in animals given MGV with a GMT of 5.5 which was 45.3% higher than animals given SGV.
Keywords: Immunization; Boophilus microplus; rabbits; midgut; salivary glands